A new progressive damage model for predicting the tensile behavior of the three-dimensional woven carbon/carbon composites using micromechanics method. (February 2022) - Wei, Kunlong; Shi, Hongbin; Li, Jiang; Tang, Min
A new progressive damage model for the three-dimensional (3 D) woven carbon/carbon (C/C) composites is developed at fiber-matrix level using the micromechanics method. A woven architecture based Representative Volume Element (RVE) model composed of yarns, matrix and yarn/matrix interface is constructed, in which the manufacturing void defects are accounted for. The fiber-matrix concentric cylinder model is employed as a repeating unit cell to represent the yarn, and the matrix micro strain field is computed analytically by the micromechanics method. The maximum stain criteria is utilized for fiber longitudinal breakage, and the Von-Mises criterion is applied for the damage initiation of matrix in both intra-yarns and inter-yarns. The damaged fiber and matrix are modeled by the stiffness degradation method combined with exponential damage evolution equations. The zero thickness cohesive elements governed by bilinear traction-separation constitutive are adopted for yarn/matrix interfacial debonding behavior. The micro progressive damage and failure behavior of the 3 D woven C/C composites subjected to tension is implemented through a developed user-defined material subroutine in commercial software ABAQUS. The predicted stress-strain response is in a good agreement with experimental results. In addition, the effect of manufacturing void defects is also examined by the developed model.